Scaling of Experimental Buoyancy Vortex Structures with Respect to Power Generation. Issue 3 (September 2020) - Hawkes, N.A.; Flay, R.G.J.; Cater, J.E.; Macdonald, M.
Abstract: A scaling or nondimensionalisation of atmospheric buoyancy vortices for power generation (based on the Oberbeck-Boussinesq assumption) is proposed that uses a published formulation from the study of Rotating Rayleigh-Benard Convection. This is combined with assumptions that the vortex flows are pseudo-cyclostrophic and that a radial Richardson number can serve as a predictor of the onset of Kelvin-Helmholtz instability leading to a transition to a turbulent plume, in order to locate the cold reservoir of the vortex when viewed as a heat engine. This permits the prediction of the behaviour of large vortices in atmosphere using data from experiments on small vortices.